SEMINAR PENGENALAN DAN PEMAHAMAN 3 DOSA BESAR PENDIDIKAN DI SMKS ARRASYADIYYAH - Surani, Dewi; Handoyo, Alfiandy Warih; Zakiyyah, Najma; Jauza, Ratu Hanifa; Damayanti, Ianthine Putri; Saptia, Saptia (LPPM Universitas Bina Bangsa, 2024)
Bullying is one of the three cardinal sins in education that must be eradicated and prevented. The mission of education is to provide opportunities and happiness to students, a goal that can be achieved by preventing bullying. This research aims to understand and introduce the concept of the three cardinal sins in education with the aim of instilling character values in students. There are still many students in Indonesia who do not understand the essence of the concept of the three cardinal sins in education. The purpose of this activity is to evaluate and find prevention strategies against the three major sins in education at Arrasyadiyyah SMKS. The method used in this activity is a seminar or lecture (presentation) to raise students' awareness. It helps students understand the three major sins, their causes, negative impacts, prevention efforts, as well as broaden their personality horizons. The results of this activity show that students can learn about the impact of bullying, sexual violence, and intolerance, as well as how to prevent and eliminate these behaviours. The school and the teaching campus team made an effort by providing a special place and inviting presenters from the Guidance and Counselling study programme lecturers to provide material on the introduction and understanding of the three cardinal sins in education, with a focus on bullying. This socialisation involved 78 students from classes X OTKP, X TBSM, XI OTKP, XI TBSM, and the SMK teachers. This activity was carried out on Tuesday, 21 May 2024, in person and face-to-face